AN EVALUATION OF PUBLIC SECONDARY SCHOOLS’ EDUCATION FINANCING AND ITS IMPACT ON SERVICE QUALITY IN LUSAKA, ZAMBIA - Hapompwe, Chrine, C.; Karim, FCGIA, Prof. Dr. Asif Mahbub; Milimo, MA, Vision; Kambikambi, PhD, Dr. Tamala-Tonga (African Journal of Education and Practice, 2020)
Purpose: This paper was purposed to evaluate public secondary schools' education financing and its impact on service quality in the Lusaka district of the Republic of Zambia. Methodology: It employed desk review and expert analysis as methodological paradigms. Findings: From the literature gathered and analysed, it has been established that the MoGE sector's financing from central government from 2015 to 2019 has been steadily declining from 20.2% in 2015 to 15.1% in 2019, contrary to UNESCO's sacrosanct global benchmark of 20% minimum annual appropriation for the sector for its service quality needs in the said subsector. The study has also identified financial inadequacies and weak controls within the sector in that funds meant for school supplies /materials and infrastructure expansion and construction have severally been misapplied and misappropriated to the detriment of the Subsector. Besides, there is literature prima facie evidence, coupled with government's anecdotal pronouncements pointing to donors' withdrawal of financing to the sector and the country's known huge public debt stock as being causal factors to the dwindling financing trend. Results: With all these occurrences and based on comparative literature evidence in the similar situations, it has been benchmarked that the service offerings within the subsector has been marred with unimaginable compromises in terms of quality, accessibility, affordability, accountability and relevance. To this effect, and as simply a randomized partial resultant indicator, disaggregated statistics have revealed that even the number of children out of school has soared from 195,000 in 2015 to about 800,000 in 2018 - a record which is unprecedented in the history of the education sector in Zambia. Unique contribution: The paper strongly implores central government to take pragmatic policy measures aimed at curtailing the phenomena, including but not limited to, instilling seemingly lost confidence by the donors in financing the sector and diversifying the subsector's financing model.